Age Is Not a Limiting Factor in Interventional Radiotherapy (Brachytherapy) for Patients with Localized Cancer. (21st January 2018) - Lancellotta, Valentina; Kovács, György; Tagliaferri, Luca; Perrucci, Elisabetta; Colloca, Giuseppe; Valentini, Vincenzo; Aristei, Cynthia
Abstract : This review examines the role of interventional radiotherapy (IRT otherwise known as brachytherapy) in cancer treatment for elderly patients. Despite their advanced age and associated comorbidities, elderly patients should receive definitive cancer therapies, including surgery and radiotherapy (RT). In fact, RT becomes first-line option for patients who are not eligible for surgery (due to comorbidities, anticoagulant drugs, and risk of disfigurement) or those who refuse it. It emerged from this review of the literature as effective, simple, safe, and comfortable and was associated with good local control, low toxicity rates, and excellent cosmesis and provided a cost benefit. IRT may be used as sole treatment for small cancers or as a useful adjunct to surgery or external beam radiotherapy (EBRT) in more advanced (or lymph node positive) cases, especially when the aim is local control with adequate preservation of normal tissue function. As palliative treatment, IRT preserves quality of life and/or improves survival. It is to be hoped that this review will serve as a helpful guide for members of multidisciplinary teams that are involved in treating elderly patients with cancer.